Compressible colloidal clusters from Pickering emulsions and their DNA functionalization. Issue 60 (4th July 2018) - Jo, In-Seong; Oh, Joon Suk; Kim, Shin-Hyun; Pine, David J.; Yi, Gi-Ra
Abstract : Colloidal clusters were prepared by assembling azide-functionalized non-crosslinked polymer particles using fluorinated oil-in-water emulsion droplets. Abstract : Colloidal clusters were prepared by assembling azide-functionalized non-crosslinked polymer particles using fluorinated oil-in-water emulsion droplets. The particles were adsorbed onto the droplet interface, which were packed to form clusters during slow evaporation of the oil. Then, the clusters were coated by DNA using an alkyne–azide cycloaddition (SPAAC) reaction. As the particles are not crosslinked, the shape of the DNA-coated clusters can be further modified to control the compression ratio through plasticization.